(untitled) (Journal on Geoinformatics, Nepal, 2002)
Multi resolution geodatabase will support diverse application requirements ranging in scale and resolution. Creation of such a database primarily enhances production of derived maps, which is one of the key application areas within NGII context. The paper identifies the processes involved specifically in the area of production of derived maps.